Inversión de capital y generación de valor en empresas constructoras de edificios del departamento del Atlántico, Colombia, en el período 2016-2021 (2023)
Capital investment is considered an essential issue for companies growth and sustainability due to its influence on utilities, moreover returns on assets is a value creator inductor for companies. Objectives. To analyze the relationship between capital investment and value creation for building construction companies in the department of Atlántico. Methods. Longitudinal analysis for the 18 companies of the department of Atlántico for the period 2016-2021, using value creation as an independent variable. It required to vertical analysis, horizontal analysis, financial key performance indicators, and statistics analysis of studied variables: Value creation and Capital investment. Results. It is found a weak correlation between Value creation and Capital investment in the building companies of the department of Atlántico with a negative correlation (p=0, 2964). Conclusions. Related studies to Value creation have integrated several variables like capital investment, fixed asset productivity and cost of capital in different production sectors. Considering the differences among sectors such as food sector or manufacturing sector, strong relationship has been found between studied variables, however, in the construction industry of the department of Atlántico it cannot be taken into account capital investment as a unique variable of value creation due to the business model and proper dynamic sector.